(untitled) (Impact: Journal of Transformation, 2022)
This study investigated the impact of the COVID-19 pandemic on the psychosocial well-being of college students studying at the Africa International University, Karen, Nairobi County, Kenya. The objectives of the study were: to establish the prevalence of preventive hygiene measures by students due to the COVID-19 pandemic, to assess whether the COVID-19 pandemic causes depression, to determine the severity of anxiety due to the COVID-19 pandemic and to investigate the prevalence of avoidance behavior due to the COVID-19 pandemic by students of AIU, Karen, Nairobi, Kenya. The study employed a descriptive survey research design in which a sample size of 123 respondents was selected from a target population of 1134 students using the stratified random sampling method. A structured questionnaire including the Becks Depression Inventory-II and Beck’s Anxiety Inventory tools was used to collect data from the respondents. The results showed that the COVID-19 pandemic significantly impacted the psychosocial well-being of college students. More than 60% of the students incorporated behavior changes and adhered to the government directives on preventive hygiene measures. It was also found that the students suffered from depression at 20.10 ± 0.975SD. The student also suffered from anxiety at 15.85 ± 0.491SD. Avoidance behavior was also prevalent at p = 0.000. The study recommends the introduction of psychoeducation programs to educate the students on how to cope with the COVID-19 pandemic and other pandemics that might occur, initiation of accessible and affordable counselling services for students, training on developing resilience, a concerted effort between the colleges and government to educate students on how to cope with pandemics and that the government should put measures to mitigate the spread of fake news from social media and educate people on where to obtain reliable information.